Pemberdayaan Masyarakat Dalam Rangka Penguatan Ekonomi Desa - Benny Arif Pamburdiarto (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Kebomas District, Gresik Regency is the lack of awareness of the potential around them that they might be able to use as additional resources to be useful for the education of the people of Randuagung Village. One of the programs implemented in RW 009 in Randuagung Village is Community Learning Guidance. The objectives of holding the BIMBEL program are: To create public awareness of the importance of knowledge; To create quality, character, creative and innovative Human Resources; To encourage and motivate children to be passionate about learning and achieving achievements. The result of this Bimbel program is that the children are enthusiastic in participating in these activities. In addition, this Bimbel program can also help students who have difficulty working on practice questions given during learning activities at school.